Способ получения низших олефинов из легкого углеводородного сырья - Ерофеев В. И. Владимир Иванович; Ермизин К. В. Константин Владимирович; Кузнецов Н. Н. Николай Николаевич; Маскаев Г. П. Геннадий Павлович; Коваль Л. М. Любовь Михайловна
опубл. 20.06.08